Legal bases of formation and development of transport Prosecutor’s office of Kazakhstan - Sidorova, N.V.; Magdatova, K.Zh.; Meirmanova, D.Sh. (Bulletin of the Karaganda University “Law Series”, 2020)
The article deals with the legal basis of the formation and development of the transport Prosecutor’s office of Kazakhstan. The purpose of this study is to determine the historical and legal prerequisites for the creation and functioning of the transport Prosecutor’s office as a specialized body of the system of Prosecutor’s offices of Kazakhstan. The main emphasis is made on the study of archival materials reflecting the main stages of specialization of the Prosecutor’s office of Kazakhstan on transport supervision. The methodological basis of this work consists of systematic approaches to the study of legal acts reflecting the history of the transport Prosecutor’s office, as well as General scientific methods of knowledge. The conducted research allowed to draw a conclusion that the transport Prosecutor’s office was created proceeding from needs of development of economy, society and the state. The study of the formation and development of the transport Prosecutor’s office of the Republic of Kazakhstan allowed the authors to justify the historical purpose of this body and its place in the system of prosecution through the prism of the need to perform the functions assigned to the transport Prosecutor’s office in accordance with the legislation of the Republic of Kazakhstan and the needs of society. Research of historical aspects of formation and development of bodies of transport Prosecutor’s office allows to formulate conclusions and the offers directed on improvement of legal and organizational bases of activity